2016
DOI: 10.5194/amt-9-1627-2016
|View full text |Cite
|
Sign up to set email alerts
|

The detection of carbon dioxide leaks using quasi-tomographic laser absorption spectroscopy measurements in variable wind

Abstract: Laser absorption spectroscopy (LAS) has been used over the last several decades for the measurement of trace gasses in the atmosphere. For over a decade, LAS measurements from multiple sources and tens of retroreflectors have been combined with sparse-sample tomography methods to estimate the 2-D distribution of trace gas concentrations and underlying fluxes from point-like sources. In this work, we consider the ability of such a system to detect and estimate the position and rate of a single point leak which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…While traditional tomographic applications employ large numbers of back projections (chords) and angles that approach or exceed the number of pixel elements in the resulting 2-D image, this application is under-sampled due to the number of deployed transceivers and reflectors, site topography, and both natural and man-made barriers. This approach, detailed in Dobler et al (2017), is similar to those proposed and implemented in Levine et al (2016), Cuccoli et al (2009), and Giuli et al (1991Giuli et al ( , 1999. The data were archived for post-deployment analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While traditional tomographic applications employ large numbers of back projections (chords) and angles that approach or exceed the number of pixel elements in the resulting 2-D image, this application is under-sampled due to the number of deployed transceivers and reflectors, site topography, and both natural and man-made barriers. This approach, detailed in Dobler et al (2017), is similar to those proposed and implemented in Levine et al (2016), Cuccoli et al (2009), and Giuli et al (1991Giuli et al ( , 1999. The data were archived for post-deployment analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike point source measurements that can be calibrated using synthetic input gas with known concentrations traceable to an established standard, these technologies have no well-established mechanism for cross-comparison to a traceable standard reference. In the interim, in order to effectively compare these data with other quasi-collocated highprecision in situ measurements, to incorporate the retrieved long-path concentration values into standardized GHG flux modeling frameworks (Broquet et al, 2011;Göckede et al, 2010;Nehrkorn et al, 2010), or to provide meaningful 2-D maps of concentrations or flux distributions over the field of view, quasi-stationary biases between the different measurement types (e.g., those from established in situ instruments and a long-path differential absorption spectrometer like GreenLITE ™ ) must be addressed. The observed slowing varying biases or differences between the GreenLITE ™ and in situ measurements may be attributed to several sources.…”
Section: Introductionmentioning
confidence: 99%
“…Early work has also been done to use the time varying horizontal wind information, combined with the spatial concentration information, to track and identify plume source location with potential for determining plume strengths. 6 A number of LiDAR approaches, such as that demonstrated by Repasky et al, 7 provide close corollaries to the GreenLITE measurement, but GreenLITE is distinctly different in its implementation of intensity modulated continuous wave (IM-CW) laser absorption spectroscopy. While both approaches exploit the differences in atmospheric transmission for two closely spaced, narrow laser lines and benefit from the cancellation of common-mode terms due to other processes (primarily scattering) that are nearly identical at both wavelengths, the other approaches use atmospheric backscatter to provide spatially resolved information.…”
Section: Introductionmentioning
confidence: 99%
“…The current industry practice for leak detection and repair (LDAR) is to perform infrequent (annual or less for most sites) 15 "spot" checks for leaks, for example by visual inspection with an optical gas imaging (OGI) camera. However, recent work has shown that methane concentrations measured by OGI cameras can be drastically underestimated if conditions are not ideal, for example if temperatures are cold, wind speeds are high, or viewing distances are greater than 50 m (Ravikumar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of trace gases 30 along the open beam path is determined from the species-specific absorption of light (Dobler et al, 2015;Flesch et al, 2004;Groth et al, 2015;Hashmonay et al, 1999;Levine et al, 2016). The laser is a dual frequency comb spectrometer: a unique broadband, high-resolution spectrometer that offers very high stability (low drift) and measurement reproducibility (close Atmos.…”
Section: Introductionmentioning
confidence: 99%